(3GdGSJOQGc aj GdBNP Ydi GdeBNP GdcfOjI ef GdeYGfj GdWGFjIs - (3CHhGdaJM fUQGddg Hf eMeO Hf eMeO Hf YHO GdcQje GdTjHGfjs; (3SYjO Hf GdeHGQc Hf Ydj GdCfUGQj, CHh eMeO, GdeYQha HGHf GdOgGf,J (B569 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3hbaJ Ydi cJGH ef JCdja CHj eMeO SYjO GdHZOGOj hSeg HGdeBNP GdcfOjI hdeG hLOJ CHf GdOgGf bO Cda cJGHg GdehShe HGdeBNP CfTCJ cJGHj gPG s
(3BNQgG (B:s
(3hCfJ GdPj jZTi GdCSfI ebOeG EPG MGV Yf eqO GdefjI MGFV s
(3YdjgG Jedjc SfI (B690(3g`s
(3fSNI fajSI LOkG hgj GdfSNI GdhMjOI aj GdYGdes
(3gfGc Tc aj CfgG ocJHJ HNW eDdagGs
(3hGdeBNP GdcfOjI gj dCHj eMeO SYjO Hf GdeHGQc Hf Ydj GdCfUGQjs
(3GdeYQha HGHf GdOgGfs
(3GdeJhai SfI (B569(3g` s
Keywords: (3GdCOHs